81 Why do patients with concomitant HF and COPD return to hospital? risk factors and reasons for short-term readmission. (May 2019) - Gulea, Claudia; Zakeri, Rosita; Quint, Jennifer K
Abstract : Background: COPD is one of the most frequent comorbidties in HF and COPD exacerbations are a competing cause of hospitalisation in this patient group. We evaluated the causes and predictors of 30-day readmission in a large population of patients hospitalised for HF with comorbid COPD. Methods: We identified 54, 953 patients hospitalised for HF with a comorbid diagnosis of COPD in the National Readmissions Database in the United States, in 2012. Using Cox proportional hazards regressions we evaluated factors associated with 30-day all-cause, respiratory and cardiovascular (CV)-related readmissions. The primary cause of readmission was identified using ICD–9CM codes. Results: The most common cause for readmission was CV (50.5%), while the most frequent cause for non-CV readmission was respiratory disease (13%). Factors associated with 30-day all-cause readmission included: Renal failure (HR 1.24, 95% CI 1.19 - 1.30), anaemia (HR 1.14, 95% CI 1.09 - 1.19), weight loss (HR 1.14, 95% CI 1.05 - 1.24), diabetes (HR 1.09, 95% CI 1.04 - 1.14), and index hospitalisation length of stay over 10 days (HR 1.45, 95%CI 1.36 - 1.55, Figure 1). Respiratory-related readmission was positively associated with recent weight loss (HR 1.37, 95% CI 1.09 - 1.71), depression (HR 1.21, 95% CI 1.02 - 1.44), obesity (HR 1.17, 95% CI 1.02 - 1.36) and length of stay over 10 days (HR 1.86, 95% CI 1.54 - 2.25). Major risk factors for CV readmission were renal failure (HR 1.42, 95% CI 1.33 - 1.51), coronary artery disease (HR 1.18, 95%CI 1.11 - 1.26) and diabetes (HR 1.18, 95% CI 1.10 - 1.24). Conclusion: In patients hospitalised for HF with comorbid COPD, most readmissions are still due to a CV cause; however, several non-cardiac risk factors significantly contribute to readmission risk. These data highlight an opportunity to better assess and treat non-cardiac comorbidities in order to reduce readmissions in this high-risk population. Conflict of Interest: None